Buffer capacity allocation: a method to QoS support on MPLS networks - Huerta, Mónica Karel; Padilla, Jhon; Hesselbach, Xavier; Fabregat, Ramón; Ravelo, Oswaldo (Revista Colombiana de Computación, 2006)
This paper describes an optimized model to support QoS by mean of Congestion minimization on LSPs (Label Switching Path). In order to perform this model, we start from a CFA (Capacity and Flow Allocation) model. As this model does not consider the buffer size to calculate the capacity cost, our model- named BCA (Buffer Capacity Allocation)- take into account this issue and it improve the CFA performance. To test our proposal, we perform several simulations; results show that BCA model minimizes LSP congestion and uniformly distributes flows on the network. Keywords: MPLS, QOS, Buffer allocation.